Flannery O'Connor : the cartoons - O'Connor, Flannery (Fantagraphics ; Turnaround [distributor], 2012)
Reveals that author Flannery O'Connor originally wanted to be a cartoonist and collects her early comics, which display many of the story-telling techniques that she later used in her writing.